Scalable Process for High-Yield Production of PfCyRPA Using Insect Cells for Inclusion in a Malaria Virosome-Based Vaccine Candidate - Fernandes, Bárbara; Sousa, Marcos; Castro, Rute; Schäfer, Anja; Hauser, Julia; Schulze, Kai; Amacker, Mario; Tamborrini, Marco; Pluschke, Gerd; Alves, Paula M; Fleury, Sylvain; Roldão, António (Frontiers in Bioengineering and Biotechnology, 2022)
The Plasmodium falciparum cysteine-rich protective antigen (PfCyRPA) has been identified as a promising blood-stage candidate antigen to include into a broadly cross-reactive malaria vaccine. In the last couple of decades substantial effort has been committed in the development of scalable cost-effective, robust and high-yield PfCyRPA production processes. Despite insect cells being a suitable expression system due to its track record for protein production (including vaccine antigens), these are yet to be explored to produce this antigen. In this study, different insect cell lines, culture conditions (baculovirus infection strategy, supplementation schemes, culture temperature modulation) and purification strategies (affinity tags) were explored aiming to develop a scalable, high-yield and -quality PfCyRPA for inclusion in a virosome-based malaria vaccine candidate. Supplementation with antioxidants improved PfCyRPA volumetric titers by 50%, when added at the time of infection. In addition, from three different affinity tags (6x-His, 4x-His and C-tag) evaluated, the 4x-His affinity tag was the one leading to highest PfCyRPA purification recovery yields (61%) and production yield (26 mg/L vs 21 and 13 mg/L for 6x-His and C-tag, respectively). Noteworthy, PfCyRPA expressed using High Five cells did not show differences in protein quality or stability when compared to its human HEK293 cells counterpart. When formulated in a lipid-based virosome nanoparticle, immunized rabbits developed functional anti-PfCyRPA antibodies that impeded multiplication of P. falciparum in vitro. This work demonstrates the potential of using IC-BEVS as a qualified platform to produce functional recombinant PfCyRPA protein with the added benefit of being a non-human expression system with short bioprocessing times and high expression levels.